2010
DOI: 10.1002/poc.1815
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of bicyclo[2.2.1]hept‐5‐ene‐endo‐2‐ylmethylamine and nitrophenyl glycidyl ethers

Abstract: Reactions of 2‐nitro‐, 4‐nitro‐ and 2,4‐dinitrophenylglycidyl ethers with bicyclo[2.2.1]hept‐5‐ene‐endo‐2‐ylmethylamine in isopropanol have been studied. The mixtures of products were chromatographed on silica gel and eluted with ether or ether/2‐propanol (1:1), the structures of individual products have been confirmed by IR spectra, NMR 1H, 13C spectra, using experiments that involve homonuclear and heteronuclear scalar coupling interactions (COSY, TOCSY, HMQC, HMBC), and mass spectrometry. Amino alcohols as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…53 A small amount of disubstituted product and some aromatic substitution product were formed in the reactions. Theoretical calculations at the B3LYP/6-311+G(d,p) level in the gas phase and using the IEFPCM model to account for the solvent supported the experimental results.…”
Section: Reactions Of Cyclic Ethersmentioning
confidence: 99%
See 1 more Smart Citation
“…53 A small amount of disubstituted product and some aromatic substitution product were formed in the reactions. Theoretical calculations at the B3LYP/6-311+G(d,p) level in the gas phase and using the IEFPCM model to account for the solvent supported the experimental results.…”
Section: Reactions Of Cyclic Ethersmentioning
confidence: 99%
“…107 The analysis of the reactions of many ambident nucleophiles with a variety of substrates indicates that Marcus theory, which derives Discussed earlier have been substituent effects: on the Grignard reagent and on the nitrogen of the chiral N-hetereocyclic carbene ligand−Cu(I) catalyst in the S N 2 reaction between an aryl Grignard reagent and γ -alkyl allyl bromide; 19 on the (salen)Coee and amine-co-catalysed enantioselective ring opening of para-substituted styrene oxides by fluoride ion; 48 on the bonding, electron density at the reacting atoms, atomic ee charges on the atoms, the source function, and the intermolecular interactions in epoxides; 51 on the regiospecific S N 2 ring-opening reaction of ortho-and para-nitro-or 2,4-dinitrophenylglycidyl ethers by bicyclo[2.2.1]hept-5-ene-endo-2-ylmethylamine in 2-propanol; 53 on the secondary αand perdeutero-deuterium KIEs, E2/S N 2 ratios, reaction efficiencies, transition-state looseness parameters, and the relative basicities of the nucleophiles in the gas-phase reactions between methyl, ethyl, i-propyl, and t-butyl iodides and SH − , Cl − , and CN − ; 77 on the S N reactions between m-and p-X-substituted benzyl amines and N-methyl-α-bromo-p-Y-substituted acetanilides in DMSO; 78 on the α-effect for the gas-phase S N 2 reactions between HOO − versus MeO − , OH − , or EtO − and methyl fluoride, anisole, and 4-fluoroanisole; 82 on the gas-phase S N 2 reactions between dimethylmethylphosphonate and methylformate and HOO − versus HO − , MeO − , or EtO − in an attempt to discover the origin of the α-effect; 83 on the S N 2 reaction of carbanions with 4-substituted benzyl chlorides in liquid ammonia; 84 on the solvolysis reaction 85,86 and the S N 2 reaction between phenoxide ions, and both neutral and negatively charged amines and 4-substituted benzyl chlorides in liquid ammonia; 85 on the ionization rates (the k 1 step) of the S N 1 reactions of many substituted trityl halides and carboxylates in aqueous acetone and in aqueous and pure acetonitrile in the presence of piperidine; 90 on the ionization rates (k 1 ) of the S N 1 reactions of various diarylmethyl chlorides in the presence of piperidine, pyridine, or PPh 3 in several dipolar aprotic solvents; 91 on the solvolyses of X,Y-substituted benzhydryl acetates in various aqueous MeOH and EtOH solutions; 92 and on the dispersions observed in Grunwald-Winstein correlations of S N 1 solvolyses of substrates with substituents containing adjacent π -electrons. 96…”
Section: Structural Effectsmentioning
confidence: 99%
“…Experimental studies [14,15] have shown that the interaction of amine ((1S,2S,4S)-bicyclo[2.2.1]hept-5en-2-ylmethanamine (1) with epoxides (2-((cyclohexyloxy)methyl)oxirane (2), 2-(phenoxymethyl)oxirane…”
Section: Introductionmentioning
confidence: 99%
“…Oxiranes reactions with OH‐acids are widely used for synthesis of the epoxy resin monomers, pharmaceutical substances and are a convenient model for studying detoxification of oxirane compounds in biological systems:…”
Section: Introductionmentioning
confidence: 99%